2015
DOI: 10.2151/sola.2015-032
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Monthly Variation in Snowfall over Complicated Mountainous Areas around Japan's Northern Alps

Abstract: We investigated the seasonal variation of snow cover at different altitudes using station data, satellite data, and a high-resolution numerical model around the Japan's Northern Alps during three winters (2011/12, 2012/13, and 2013/14). The satellite data showed that the snow cover fraction was largest in 2012/13 before late December, which indicates that much of snowfall occurs at higher elevations in the early winter. In midwinter, the snow cover fraction was over 90% in 2011/12, while it was approximately 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This means that the weakened winter monsoon reduces the precipitation over the coastal areas of the Sea of Japan and activates extratropical cyclones passing south of Japan, which brings precipitation over the coastal areas of the Pacific Ocean. The weakening of the winter monsoon due to global warming has been pointed out in previous studies (e.g., Hu et al 2000;Kimoto 2005;Hori and Ueda 2006;Kawase et al 2015). In addition, future changes in mid-winter storm tracks affect the winter precipitation in Japan.…”
Section: Changes In Daily Snowfall Intensitymentioning
confidence: 73%
See 2 more Smart Citations
“…This means that the weakened winter monsoon reduces the precipitation over the coastal areas of the Sea of Japan and activates extratropical cyclones passing south of Japan, which brings precipitation over the coastal areas of the Pacific Ocean. The weakening of the winter monsoon due to global warming has been pointed out in previous studies (e.g., Hu et al 2000;Kimoto 2005;Hori and Ueda 2006;Kawase et al 2015). In addition, future changes in mid-winter storm tracks affect the winter precipitation in Japan.…”
Section: Changes In Daily Snowfall Intensitymentioning
confidence: 73%
“…In Japan's Northern Alps, at Murododaira ( Fig. 1d), whose altitude is 2450 m above sea level (mASL), the snow depth and snow water equivalent (SWE) are about 600 cm and 3000 mm, respectively, in early spring (Aoki and Watanabe 2009;Kawase et al 2015Kawase et al , 2018bKawase et al , 2019a. Enormous SWEs in the mountainous areas are available as water resources in the spring and early summer in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigate the extremely small amounts of snow observed at high elevations in the 2015/16 winter and interannual variations of snow cover from 2000/01 to 2015/16 in the Japanese Northern Alps. We use a regional climate model, which is useful tools for simulating the snow cover in mountainous areas (Hara et al 2008;Rasmussen et al 2011;Kawase et al 2015). The specifications of the numerical simulation and overviews of snow-cover observations are presented in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed process connecting the large-scale circulation anomalies to individual snowfall events accompanied by a convective system: Here, we could not investigate the mesoscale fields associated with the large-scale circulations, since it was difficult to sufficiently investigate such small and short scale processes in the global reanalysis. Using radar and mesoscale analysis data and dynamical downscaling approaches using convection-permitting models may be promising (e.g., Nakai et al 2005;Kawase et al 2015;Kayaba et al 2016;Fukui et al 2018).…”
Section: Discussionmentioning
confidence: 99%